2012
DOI: 10.5539/elt.v5n11p151
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Practice and Cultural Difference of an English as Foreign Language Classroom in Taiwan

Abstract: Uninterrupted interactions of merchants and travelers from different countries stress the significance of English. The purpose of the study was to investigate what cultures and teaching practices are different between native English-speaking teachers and Taiwanese senior high school students. Three native English-speaking teachers and six Taiwanese senior high school students in Taichung city participated in this study. Data were collected through native English-speaking teachers' and Taiwanese senior high sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In Chinese college English writing, teacher feedback dominates while peer feedback and automated feedback are less frequently used (Bai, 2012;Zhou, 2013), which compromises the efficacy of feedback in facilitating students' writing competence. Recently, with student-centered teaching philosophy gradually accepted, peer feedback has been paid increasing attention to and practiced in language classes for its great significance in motivating students' participation, cultivating their critical thinking and developing their ability of self-regulated learning (Plank & Condliffe, 2011;Bai, 2012;Liao & Yang, 2012;Forrer et al, 2015;Wang, 2016). Studies on peer feedback have revealed students can also be an information-and-assistance provider in L2 writing (Leggette et al, 2013;Wang, 2016), for they have sufficient time, energy and resource (Andrade, 2008;Cho & Schunn, 2010;Luo, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In Chinese college English writing, teacher feedback dominates while peer feedback and automated feedback are less frequently used (Bai, 2012;Zhou, 2013), which compromises the efficacy of feedback in facilitating students' writing competence. Recently, with student-centered teaching philosophy gradually accepted, peer feedback has been paid increasing attention to and practiced in language classes for its great significance in motivating students' participation, cultivating their critical thinking and developing their ability of self-regulated learning (Plank & Condliffe, 2011;Bai, 2012;Liao & Yang, 2012;Forrer et al, 2015;Wang, 2016). Studies on peer feedback have revealed students can also be an information-and-assistance provider in L2 writing (Leggette et al, 2013;Wang, 2016), for they have sufficient time, energy and resource (Andrade, 2008;Cho & Schunn, 2010;Luo, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Old and North-Korean-Oriented Language …they all me old Korean or grandmother in my soul…I don't feel positive…because they laugh at my language application…as a Korean…using old-schooled languages…what is my wrong? (Participant #5,Focus Group Activity) Like many other languages, the differences between written and spoken Korean languages may increase difficulty and confusion for native and non-native speakers (Liao & Yang, 2012;Sun et al, 2016). According to a previous study (Gao, 2010), Korean-Chinese residents usually learn Korean from family members, school teachers, and textbook materials.…”
Section: Speak the Textbook Korean Languagesmentioning
confidence: 99%
“…Similar to Japan and South Korea, 400 certified foreign English teachers have been hired in the public schools to co-teach with local English teachers, beginning in August 2003 (Chang et al, 2005;Chern, 2010). Since 2002, English class has been introduced since grade one in metropolitan elementary schools with the objective to instill a basic communicative ability (Butler, 2009;Liao and Yang, 2012;Nunan, 2003). This plan included some of the following aspects: 1) use curriculum guidelines and open market for textbooks; 2) provide multiple possibilities for teachers to become certified; 3) advocate the communicative approach in English (cf.…”
Section: Taiwanmentioning
confidence: 99%
“…It is important to understand the peculiarities of Taiwanese students based on my longterm teaching experience and observation. They prefer a lecture instead of discussion, so being silent in the class without asking or answering questions or having a discussion is normal for the Taiwanese students (Huang & Brown, 2009;Liao & Yang, 2012;Young, 2003). It could be explained due to their fear of failure giving the wrong answer and by thus "losing the face" in front of others, also due to their shyness and resistance towards communication, public speaking, etc.…”
Section: Taiwanmentioning
confidence: 99%